Correction: Understanding MAOS through computational chemistry. (31st March 2017) - Prieto, P.; de la Hoz, A.; Díaz-Ortiz, A.; Rodríguez, A. M.
Abstract : Correction for 'Understanding MAOS through computational chemistry' by P. Prieto et al., Chem. Soc. Rev., 2017, 46, 431–451.